The missing conformer: A comprehensive rotational spectroscopy study and astronomical search of two conformers of methyl cyanoacetate - Batra, Gayatri; Pinacho, Pablo; Steber, Amanda L.; Rivilla, Víctor M.; Martín-Pintado, Jesús; Jiménez-Serra, Izaskun; Schnell, Melanie (Frontiers in Astronomy and Space Sciences, 2022)
We performed a comprehensive investigation of methyl cyanoacetate (MCA) using high-resolution Fourier transform rotational spectroscopy. Two low energy conformers of MCA were observed in the vibrational ground state, in selected frequency regions from 2 to 110 GHz. We report accurately determined line lists, rotational constants, centrifugal distortion constants, and nuclear quadrupole coupling constants for both conformers, as well as for several singly substituted heavy-atom isotopologues. Despite the fact that the second conformer is higher in energy by 1.4 kJ/mol with respect to the global minimum, the transition intensities of the former are observed to be more intense than the lowest energy conformer. This effect due to the difference in the dipole moment components is also observed in the experimental spectrum, both in the low- and high-frequency regions. The accurate predictions of rotational transitions into the millimeter-wave region can facilitate the detection of these conformers of MCA in the interstellar medium. Using the rotational spectroscopy data provided here, we searched for the two conformers of MCA in a deep and unbiased spectral survey of the molecular cloud G+0.693-0.027 located in the Galactic Center. None of the MCA conformers were detected. The upper limits for their abundances were derived with respect to the abundance of molecular hydrogen.